Molecular Dissection of Pro-Fibrotic IL11 Signaling in Cardiac and Pulmonary Fibroblasts - Widjaja, Anissa A.; Viswanathan, Sivakumar; Jinrui, Dong; Singh, Brijesh K.; Tan, Jessie; Wei Ting, Joyce Goh; Lamb, David; Shekeran, Shamini G.; George, Benjamin L.; Schafer, Sebastian; Carling, David; Adami, Eleonora; et al. (Frontiers in Molecular Biosciences, 2021)
In fibroblasts, TGFβ1 stimulates IL11 upregulation that leads to an autocrine loop of IL11-dependent pro-fibrotic protein translation. The signalling pathways downstream of IL11, which acts via IL6ST, are contentious with both STAT3 and ERK implicated. Here we dissect IL11 signaling in fibroblasts and study IL11-dependent protein synthesis pathways in the context of approved anti-fibrotic drug mechanisms of action. We show that IL11-induced ERK activation drives fibrogenesis whereas STAT3 phosphorylation (pSTAT3) is unrelated to fibroblast activation. Ironically, recombinant human IL11, which has been used extensively in mouse experiments to infer STAT3 activity downstream of IL11, increases pSTAT3 in Il11ra1 null mouse fibroblasts. Unexpectedly, inhibition of STAT3 was found to induce severe proteotoxic ER stress, generalised fibroblast dysfunction and cell death. In contrast, inhibition of ERK prevented fibroblast activation in the absence of ER stress. IL11 stimulated an axis of ERK/mTOR/P70RSK protein translation and its selectivity for Collagen 1 synthesis was ascribed to an EPRS-regulated, ribosome stalling mechanism. Surprisingly, the anti-fibrotic drug nintedanib caused dose-dependent ER stress and lesser pSTAT3 expression. Pirfenidone had no effect on ER stress whereas anti-IL11 specifically inhibited the ERK/mTOR axis while reducing ER stress. These studies define the translation-specific signaling pathways downstream of IL11, intersect immune and metabolic signaling and reveal unappreciated effects of nintedanib.